Research of Prediction of Gear Milling Force based on FEM Simulation of Oblique Cutting - Wang Lei; Zai Shouxiang; Cui Yanmei (Jixie chuandong, 2016)
Considering the milling force calculated by using mechanical model or milling finite element simulation is time- consuming and tedious,a prediction method of milling force based on the finite element simulation of oblique cutting is proposed. In this method,each cutting edge of the cutter is discretized into infinitesimal element of oblique cutting process. And through a series of oblique cutting process simulation,the relationship is fitted between the cutting force coefficients and cutting thickness. Then by geometric transformation,the obtained cutting force coefficient are applied in milling process,the instantaneous milling forces acted on the cutter are obtained finally. Comparing with the results of milling simulation,it shows that the finite element simulation method of oblique cutting can be applied to milling process,and the effectiveness of the proposed method is verified. Therefore,this method can be used for predicting cutting force in the processing of gear,and also provides a good foundation for researching surface integrity of gear machining.